Dietary and environmental factors affecting the dynamics of the gut bacteria in Tibetan Awang sheep (Ovis aries) across divergent breeding models - Wang, Yuhao; Wang, Xinping; Wang, Yirong; Liao, Songyu; Pubu, Zhaxi; Silang, Jiangcuo; Chai, Lixu; Zhao, Siyue (Frontiers in Microbiology, 2025)
IntroductionTibetan Awang sheep (Ovis aries), indigenous to the Qinghai-Tibet Plateau, are highly adapted to high-altitude environment. However, knowledge regarding their gut bacterial composition remains limited.MethodsA comprehensive 16S rRNA highthroughput sequencing was performed on fecal samples from 15 Awang sheep under pure grazing, semi-captivity, and full captivity breeding models.ResultsOur results revealed that Firmicutes and Bacteroidetes were the most abundant bacterial phyla, while Christensenellaceae_R-7_group, Romboutsia, Rikenellaceae_RC9_gut_group, Ruminococcus, and Bacteroides were prevalent genera in the gut microbiota of Awang sheep. Meanwhile, the predominant presence of Bacteroides with increasing altitude of breeding locations indirectly demonstrates its crucial role in mediating energy acquisition among Awang sheep at high altitudes. Furthermore, PCoA and ANOSIM analysis exhibited significant differences in bacterial composition across all breeding models (r > 0.6, p < 0.001). Christensenellaceae_R-7_group, Romboutsia, and Ruminococcus were significantly abundant in the pure grazing breeding model, while Rikenellaceae_RC9_gut_group and Bacteroides were more abundant in the semi-captivity breeding model. An abnormally high abundance of Acinetobacter indicated a potential risk of Acinetobacter infection in the fully captive group. The environmental association analysis exhibited that meadows diet (R2 = 0.938, Pr[>r] = 0.001) and altitude (R2 = 0.892, Pr[>r] = 0.001) had significant effects on the dominant genera, explaining a substantial proportion of the total variation in community composition.DiscussionOur study indicated that breeding conditions significantly impact the gut microbiota of Awang sheep. The environmental association analysis underscores the importance of diet and altitude in shaping the gut microbiota of Awang sheep. The present findings provide insights into the microbiota dynamics of Awang sheep and offer guidance for their scientific husbandry management.